New records of Noctuoidea (Insecta: Lepidoptera) from the South of West Siberia - Knyazev, Svyatoslav; Ivonin, Vadim; Saikina, Sofia (Zenodo, 2022)
The article presents 13 species of Noctuoidea superfamily from Omsk and Novosibirsk regions of Russia. 6 species are new to Omsk region, 8 species are new to Novosibirsk region. 4 species are new to the Russian part of the West Siberian Plain, among them,Schrankia balneorum(Alphéraky, 1880),Spodoptera exigua(Hübner, 1808),Leucochlaena fallax(Staudinger, 1870),Mythimna anderreggii(Boisduval, 1840). Authors thank K.B. Ponomarev (Omsk), O.N. Kholodov (Krasnyi Oktyabr`, Omsk Region), A.A. Sal`nik (Ermak, Omsk Region) for the good company in collecting trips in Omsk Region in 2022 and materials provided for our research.